Insights into the demographics and preferences of Chinese deaf and hard-of-hearing learners of English: A multi-modal approach - Qin, Xuewu (2025)
The field of second language acquisition has seen numerous empirical studies focusing on language teaching theories and methods for specific learner groups. However, despite recent research increasingly addressing the needs of students with disabilities, deaf and hard-of-hearing students still do not receive the same level of attention as their hearing peers (Cisźer and Kontra, 2020). Deafness or hearing impairment often results in limited access to language and information. Nevertheless, with modern technical hearing aids, researchers have highlighted the bimodal bilingual capabilities of deaf and hard-of-hearing students, underscoring their potential to learn additional languages. Grounded in the theoretical frameworks of multilingualism and plurilingualism, this thesis explores the demographic characteristics of Chinese deaf and hard-of-hearing students as English learners andtheir multi-modal language preferences in English classrooms.